2019
DOI: 10.1177/1757975919853784
|View full text |Cite
|
Sign up to set email alerts
|

‘No one ever asked us’: a feasibility study assessing the co-creation of a physical activity programme with adolescent girls

Abstract: Background: Globally, the poor activity level of adolescent girls is a public health concern. Little research has involved adolescents in the design of interventions. This study assessed the feasibility of involving girls in the co-creation of an activity programme. Methods: Thirty-one students (15–17 years old) were recruited from a post-primary school. The Behaviour Change Wheel guided intervention design, providing insights into participants’ capability, opportunity and motivation for change. Step counts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our results were similar to those from two recent negative randomized trials of BCW-informed interventions, one delivering thrombolytic therapy for stroke in Australia ( 53 ) and the other promoting physical activity among adults at risk for cardiovascular disease in the Netherlands ( 54 ). Similar to our experience, the authors of these studies found the BCW framework to be feasible and useful for rigorously selecting and specifying implementation components, as have other investigators planning trials of novel BCW-informed strategies to promote smoking cessation in China ( 55 ), encourage physical activity among adolescent girls in Ireland ( 56 ), and reduce sedentary behaviors at work in England ( 57 ). The two groups that observed implementation failures, the Australian thrombolytic therapy group and the Dutch physical activity group, identified challenges with implementation fidelity and a compressed implementation period as factors that limited engagement of the health care workers whom their implementation strategies targeted.…”
Section: Discussionsupporting
confidence: 52%
“…Our results were similar to those from two recent negative randomized trials of BCW-informed interventions, one delivering thrombolytic therapy for stroke in Australia ( 53 ) and the other promoting physical activity among adults at risk for cardiovascular disease in the Netherlands ( 54 ). Similar to our experience, the authors of these studies found the BCW framework to be feasible and useful for rigorously selecting and specifying implementation components, as have other investigators planning trials of novel BCW-informed strategies to promote smoking cessation in China ( 55 ), encourage physical activity among adolescent girls in Ireland ( 56 ), and reduce sedentary behaviors at work in England ( 57 ). The two groups that observed implementation failures, the Australian thrombolytic therapy group and the Dutch physical activity group, identified challenges with implementation fidelity and a compressed implementation period as factors that limited engagement of the health care workers whom their implementation strategies targeted.…”
Section: Discussionsupporting
confidence: 52%
“…In the last few years, co-creation is obtaining more and more attention in the context of physical activity [ 53 ], and also in the educational context, e.g., in PE [ 54 ]. It is also a good way to increase the participation of underrepresented groups or people who are not as physically active as others [ 55 , 56 ]. There is also evidence of the positive effects of cooperative planning in the sense of health promotion [ 57 ], as well as in many domains related to physical, social, and psychological variables [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-creation has been successfully implemented in several public health initiatives 5,29,32 , and may be a viable approach to addressing other complex health behaviours. For instance, involving end-users in the design of physical activity among adolescent girls provided them with a sense of autonomy and ownership 40 , which led to increased participation and effectiveness of the intervention. The success of the projects, including the co-creation activity in this study, suggests that it is crucial to have a transition from the traditional model of service delivery to a more collaborative and transparent approach involving community participation from the outset.…”
Section: Discussionmentioning
confidence: 99%